Ovarian steroid hormones modulate the expression of progesterone receptors and histone acetylation patterns in uterine leiomyoma cells. (3rd August 2017) - Sant'Anna, Gabriela dos Santos; Brum, Ilma Simoni; Branchini, Gisele; Pizzolato, Lolita Schneider; Capp, Edison; Corleta, Helena von Eye
Abstract: Uterine leiomyomas are the most common benign smooth muscle cell tumors in women. Estrogen (E2), progesterone (P4) and environmental factors play important roles in the development of these tumors. New treatments, such as mifepristone, have been proposed. We evaluated the gene expression of total ( PRT ) and B ( PRB ) progesterone receptors, and the histone acetyltransferase (HAT) and deacetylase (HDAC) activity after treatment with E2, P4 and mifepristone (RU486) in primary cell cultures from uterine leiomyoma and normal myometrium. Compared to myometrium, uterine leiomyoma cells showed an increase in PRT mRNA expression when treated with E2, and increase in PRB mRNA expression when treated with E2 and P4. Treatment with mifepristone had no significant impact on mRNA expression in these cells. The HDAC activity was higher in uterine leiomyoma compared to myometrial cells after treatment with E2 and E2 + P4 + mifepristone. HAT activity was barely detectable. Our results suggest that ovarian steroid hormones modulate PR, and mifepristone was unable to decrease PRT and PRB mRNA. The higher activity of HDAC leiomyoma cells could be involved in transcriptional repression of genes implicated in normal myometrium cell function, contributing to the maintenance and growth of uterine leiomyoma.